EVALUASI FUNGSI ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI BANTEN MASA JABATAN 2014-2019 - Ratu Ninis Haerunnisa; Natta Sanjaya (LPPM STIA Banten, 2022)
Based on Law Number 27 of 2009 concerning the composition and position of the MPR/DPR as well as the DPD and DPRD, it is stated that DPRD has the duties and functions as a legislative function, a budget function and a supervisory function. The results of the problem identification show that the Ranperda has not been fully realized, both the proposal from the DPRD and the governor, there are still regional regulations that have been canceled due to overlapping with the central authority, there is still abuse of office attached to unscrupulous members of the Banten Provincial DPRD in carrying out budget functions and the implementation is still not optimal. supervision carried out by the apparatus of DPRD. The focus of this research is the evaluation of the functions ofDPRD members in Banten Province for the 2014 2019 term of office. The design of this research is using descriptive quantitative research methods. In the descriptive test of the data through the interpretation of each item, an average of 3.19 was obtained with an interpretation of that size, the implementation of the functions of the DPRD members of the Banten Province was categorized as good. The existence of a positive and significant influence has been carried out by the functions of members of the DPRD Province of Banten. With the t-test test which got a value of 15.54. This means that Ha is accepted and Ho is rejected. It can be concluded that the success rate of evaluating the implementation of the functions of DPRD members for the Banten Province for the 2014 -2019 term is greater than 75%, which is 79%, so the Evaluation of the Functions of the Provincial DPRD Members of the Banten Provincial DPRD is said to be good.